2020
DOI: 10.1103/physrevresearch.2.013166
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-loss domain wall motion driven by a magnetocrystalline anisotropy gradient in an antiferromagnetic nanowire

Abstract: Searching for a new scheme to control the antiferromagnetic (AFM) domain wall is one of the most important issues for AFM spintronic devices. In this work, we study theoretically the domain wall motion of an AFM nanowire, driven by the axial anisotropy gradient generated by an external electric field and an electrocontrol of AFM domain wall motion in the merit of ultralow energy loss is demonstrated. The domain wall velocity depending on the anisotropy gradient magnitude and intrinsic material properties is si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…With the increase of A σ , the wall moves towards the equilibrium position rapidly, as shown in figure 5(a). Here, the wall energy denotes E DW = 2(2|J|K z ) 1/2 [22,36], with K z is the local anisotropy constant of the wall. The spatial distribution of K z is presented in the insert of figure 5(a) to help one to understand the result easier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase of A σ , the wall moves towards the equilibrium position rapidly, as shown in figure 5(a). Here, the wall energy denotes E DW = 2(2|J|K z ) 1/2 [22,36], with K z is the local anisotropy constant of the wall. The spatial distribution of K z is presented in the insert of figure 5(a) to help one to understand the result easier.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, most of the schemes based on electrical current rely on the conduction electrons and normally generate Joule heating [6,21], which result in additional power consumption and even affect the data transportation stability. Along this line, the voltage-induced magnetic anisotropy gradient which drives the wall towards the low-anisotropy side to release the free energy is much favored for energy saving [22,23]. However, a wedge-shaped substrate structure is needed to induce the anisotropy gradient, which limits the bi-directional control of the wall motion [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the VCMA effect, the voltage-controlled motion of domain walls and skyrmions has been successfully demonstrated, indicating that the domain walls and skyrmions velocity can be significantly changed by applied voltage [35][36][37][38][39][40][41]. In addition, it is found that designing the thickness of the insulating layer (anisotropy gradient can be obtained through a wedged heterostructures) could be also effectively control the domain walls and skyrmions motion [40,[42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 94%
“…In analogy with the conventional field-driven case, the magnetoelastic field can be considered as a force that pushes the DW along the direction of decreasing energy, i.e., increasing compressive strain if λ s > 0 for the in-plane-strain-gradient case. This force is proportional to the local gradient of the spatially variable quantity 18,38,39 , and its effect is essentially that of an effective (magnetoelastic) field…”
Section: Please Cite This Article Asmentioning
confidence: 99%